Unveiling CCL2 and CXCL1: Key biomarkers and therapeutic targets in idiopathic pulmonary fibrosis - Pan, Jing; Li, Guanhua; Pu, Yuanyuan; Li, Peilin; Zhou, Yan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive lung disease characterized by fibrosis and impaired lung function. Understanding the molecular mechanisms underlying IPF is crucial for developing effective therapeutic strategies. This study aims to identify differentially expressed genes (DEGs) in alveolar macrophages of IPF patients and validate these findings in an independent cohort. We analyzed gene expression data from the GSE49072 dataset, which includes 23 IPF and 61 normal alveolar macrophage samples. Differential expression analysis was performed using the LIMMA package, and Gene Set Enrichment Analysis (GSEA) identified significant biological pathways. Validation of key DEGs (CCL2, CCL7, and CXCL1) was conducted using ELISA in serum samples from an independent cohort of 50 IPF patients and 50 normal controls. Correlations with clinical parameters such as forced vital capacity (FVC) and diffusing capacity for carbon monoxide (DLCO) were also evaluated. The analysis identified several DEGs, with CCL2 and CXCL1 showing significant upregulation in IPF samples. GSEA highlighted pathways related to inflammatory responses and extracellular matrix remodeling. ELISA validation confirmed elevated serum levels of CCL2 and CXCL1 in IPF patients, correlating with reduced FVC and DLCO. CCL7 did not show significant differences between groups. Targeting these chemokines may offer new therapeutic avenues for IPF treatment. Further research is needed to explore the therapeutic potential and validate findings in larger cohorts. This study enhances our understanding of IPF pathogenesis and identifies promising targets for clinical intervention.